Analysis of a tensegrity-based weighing machine. Issue 2 (3rd May 2016) - Lin, Min; Li, Tuanjie; Ji, Zhifei
Abstract: Tensegrity systems have been used in several disciplines such as architecture, robots and antennas. However, just a few works in literature have addressed the possibility of using tensegrity systems in sensor applications. In this paper, a tensegrity-based weighing machine was proposed. An energy method was used to perform the equilibrium analysis of the machine. Then, the response of a vertical load and a torque was detailed on the basis of an energy formulation. Afterwards, the concepts of mass sensitivity and torque sensitivity were proposed to evaluate the testing performance of the tensegrity-based weighing machine. The results indicate that the machine has high mass sensitivity when the height of the top platform is small and the relationship between the vertical loads and the height of the top platform is approximately linear. Moreover, the torque sensitivity is symmetric with respect to the height of the top platform and the relationship between the torque and the rotation angle of the top platform is non-linear. This work can be offered as a benchmark when such machine is put to use.